The right touch of pitch assertiveness: Examining entrepreneurs' gender and project category fit in crowdfunding - McSweeney, Jordan J.; McSweeney, Kevin T.; Webb, Justin W.; Devers, Cynthia E. (Journal of Business Venturing, 2022)
Scholars have devoted significant attention to the role of entrepreneurs' communication, and gender in crowdfunding. Yet, how female and male entrepreneurs can effectively configure their assertive communication style and the role gender norms within project categories play in shaping crowdfunders' evaluations of entrepreneurs' communication style remains unanswered. To address this, we conduct an exploratory qualitative comparative case analysis (QCA) of 1600 entrepreneurs who pitched their ventures on Kickstarter. From prior research, we identified four distinct kinds of assertive language (certain, power, social, tentative) and explore how female and male entrepreneurs' configurations of assertive language relate to crowdfunding success and failure in male-dominated and female-dominated contexts. We found six pitch assertiveness themes, two associated with success, two associated with failure, and two where success versus failure depends on nuanced considerations of the entrepreneur's gender and the gendering of the context. Our study extends our understanding of communication and gender in crowdfunding.